An effective method to generate controllable levels of ROS for the enhancement of HUVEC proliferation using a chlorin e6-immobilized PET film as a photo-functional biomaterial. Issue 2 (13th March 2021) - Hong, Seung Hee; Koo, Min-Ah; Lee, Mi Hee; Seon, Gyeung Mi; Park, Ye Jin; Jeong, HaKyeong; Kim, Dohyun; Park, Jong-Chul
Abstract: Reactive oxygen species (ROS) are byproducts of cellular metabolism; they play a significant role as secondary messengers in cell signaling. In cells, high concentrations of ROS induce apoptosis, senescence, and contact inhibition, while low concentrations of ROS result in angiogenesis, proliferation, and cytoskeleton remodeling. Thus, controlling ROS generation is an important factor in cell biology. We designed a chlorin e6 (Ce6)-immobilized polyethylene terephthalate (PET) film (Ce6-PET) to produce extracellular ROS under red-light irradiation. The application of Ce6-PET films can regulate the generation of ROS by altering the intensity of light-emitting diode sources. We confirmed that the Ce6-PET film could effectively promote cell growth under irradiation at 500 μW/cm 2 for 30 min in human umbilical vein endothelial cells. We also found that the Ce6-PET film is more efficient in generating ROS than a Ce6-incorporated polyurethane film under the same conditions. Ce6-PET fabrication shows promise for improving the localized delivery of extracellular ROS and regulating ROS formation through the optimization of irradiation intensity.